Predictive value of 3′-deoxy-3′-18F-fluorothymidine PET in the early response to anti-programmed death-1 therapy in patients with advanced non-small cell lung cancer - Yukihiro Umeda; Miwa Morikawa; Masaki Anzai; Maiko Kadowaki; Yuko Waseda; Tetsuya Tsujikawa; Yasushi Kiyono; Hidehiko Okazawa; Tamotsu Ishizuka; Masayuki Sato; Tetsuya Mori (Journal for ImmunoTherapy of Cancer)
Background Anti-programmed death-1 (anti-PD-1) therapy has shown clinical success in patients with advanced non-small cell lung cancer (NSCLC). However, it is difficult to evaluate the early response to anti-PD-1 therapy. We determined whether changes in 3′-deoxy-3′-[18F]-fluorothymidine (18F-FLT) PET parameters before and soon after treatment initiation predicted the therapeutic effect of anti-PD-1 antibody.Methods Twenty-six patients with advanced NSCLC treated with anti-PD-1 antibody were enrolled prospectively and underwent 18F-FLT PET before and at 2 and 6 weeks after treatment initiation. Changes in maximal standardized uptake value (ΔSUVmax), proliferative tumor volume (ΔPTV) and total lesion proliferation (ΔTLP) of the lesions were calculated and evaluated for their associations with the clinical response to therapy.Results The disease control rate was 64%. Patients with non-progressive disease (non-PD) had significantly decreased TLP at 2 weeks, and decreased SUVmax, PTV, and TLP at 6 weeks, compared with those with PD, while three of eight (37.5%) patients who responded had increased TLP from baseline at 2 weeks (ie, pseudoprogression). Among the parameters that changed between baseline and 2 weeks, ΔPTV0-2 and ΔTLP0-2 had the highest accuracy (76.0%) to predict PD. Among the parameters that changed between baseline and 6 weeks, ΔSUVmax0-6, ΔPTV0-6 and ΔTLP0-6 had the highest accuracy (90.9%) to predict PD. ΔTLP0-2 (≥60%, HR 3.41, 95% CI 1.34–8.65, p=0.010) and ΔTLP0-6 (≥50%, HR 31.4, 95% CI 3.55 to 276.7, p=0.0019) were indicators of shorter progression-free survival.Conclusions Changes in 18F-FLT PET parameters may have value as an early predictive biomarker for the response to anti-PD-1 therapy in patients with NSCLC. However, it should be noted that pseudoprogression was observed in 18F-FLT PET imaging at 2 weeks after treatment initiation.Trial registration number jRCTs051180147.